2020
DOI: 10.1039/d0cc00214c
|View full text |Cite
|
Sign up to set email alerts
|

Isosmaragdyrin with an N3C2 core: stabilization of Rh(i) and organo-Pt(ii) complexes

Abstract: An isosmaragdyrin analogue with an N3C2 core was synthesized and stabilized by Rh(i) and organo-Pt(ii) complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 36 publications
1
23
0
2
Order By: Relevance
“…[12,13] Themost recent examples of the compounds fulfilling the structural criteria of expanded carbaporphyrinoids,i nclude biphenylene-incorporated hexaphyrin [14] and octaphyrins,w hich demonstrate interesting conformational variety, [14,15] or the isosmaragdyrin incorporating 2,6-di-mphenylpirydine,p rone to bind transition metals with two different coordination modes. [16] As ignificant number of expanded carbaporphyrinoids were created with the use of phenanthrene-based building blocks, [17][18][19][20] for example,3 2heterophenanthrisapphyrins, [21] helicenophyrins, [22] and diphenanthrioctaphyrin. [23] Many of the expanded carbaporphyrinoids share structural features of an archetypical hexaphyrin [24,25] framework.…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] Themost recent examples of the compounds fulfilling the structural criteria of expanded carbaporphyrinoids,i nclude biphenylene-incorporated hexaphyrin [14] and octaphyrins,w hich demonstrate interesting conformational variety, [14,15] or the isosmaragdyrin incorporating 2,6-di-mphenylpirydine,p rone to bind transition metals with two different coordination modes. [16] As ignificant number of expanded carbaporphyrinoids were created with the use of phenanthrene-based building blocks, [17][18][19][20] for example,3 2heterophenanthrisapphyrins, [21] helicenophyrins, [22] and diphenanthrioctaphyrin. [23] Many of the expanded carbaporphyrinoids share structural features of an archetypical hexaphyrin [24,25] framework.…”
Section: Introductionmentioning
confidence: 99%
“…Architecturally, the macrocycle is blended with arene and pyridine units and exhibits unprecedented properties as a rendezvous of both of the categories. 26 The core of the macrocycle is efficiently utilized to stabilize both Rh I ( 54 ) and Pt II ( 55 ) ions with distinctive bonding modes ( Figure 12 ). The Rh I ion stabilizes through NN chelation and Pt II ion through (N ∧ C)N coordination to form an organometallic complex.…”
Section: Amalgamation Of Pyridine and Benzene Embedded Porphyrinoidsmentioning
confidence: 99%
“…A perusal of literature revealed that the reports on pyridine containing porphyrinoids are still few in number. [27][28][29][30][31][32][33] Herein, we attempted to synthesize pyridine containing crowned expanded porphyrins 3 a-c but we isolated pyridine containing crowned fused expanded porphyrins 4-6 because of intramolecular fusion that occurred between two pyrrole Ns and two adjacent inverted thiophene Cs. Thus, we report the synthesis of fused expanded porphyrins 4-6 containing both pyridine and crown ether moiety as a part of macrocyclic framework and their structure, spectral, electrochemical and metal sensing properties studied by various spectral, electrochemical and computational techniques.…”
Section: Introductionmentioning
confidence: 99%